ผลของโปรแกรมส่งเสริมครอบครัวเพื่อการจัดการตนเองของผู้สูงอายุที่เป็นโรคข้อเข่าเสื่อมต่อการป้องกันการหกล้ม - ธีรพันธ์ จันทร์เป็ง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Knee osteoarthritis is a common disease among older people that causes risk of falling. Falling is a major public health problem that can affect physical health, mental health, and quality of life among older people and their families. Therefore, to promote family involvement in supporting self-management among older people with knee osteoarthritis on fall prevention is very important. This quasi-experimental study, one group pretest-posttest design, aimed to investigate the effect of a family promoting program for self-management of older persons with knee osteoarthritis on fall prevention at Si Bua Ban, Muang District, Lamphun Province, from January to March 2020. There were 23 participants who were selected through a purposive sampling method. The experimental group received a family promoting program for self-management of older persons with knee osteoarthritis for seven weeks. The program, developed by the researcher, is based on self-management theory (Creer, 2000), including health education and self-management skills practice for knee osteoarthritis and falls, thigh muscle exercises, cane skill practice, and environment management. The research instruments included 1) a family promoting program for self-management of older persons with knee osteoarthritis 2) a fall prevention guidebook for older persons with knee osteoarthritis and their families 3) a family promoting guidebook for self-management of older persons with knee osteoarthritis. The content validity index of the instruments were 0.99, 1.00 and 1.00, respectively. Instruments for collecting data included demographic questionnaires, Thai fall risk assessment test (Thai-FRAT), and the time up and go test (TUGT). The Cronbach's alpha coefficient for reliability were 0.99 and 0.98, respectively. Data were analyzed using descriptive statistics, and the McNemar test and Wilcoxon Matched Pairs Signed-Ranks Test were used to compare the risk for falling and the balance and walking ability levels of older persons with knee osteoarthritis in the community before and after recieving the program. The results of this study were as follows: 1. The number of participants at risk of falling before (n = 23) (100%) and after (n = 3) (13.05%) the family promoting program for self-management of older persons with knee osteoarthritis on fall prevention decreased. After participating in the program, the number of participants showed a statistically significant lower level of risk of falling (p<0.001). 2. The number of participants at a level of balance and walking ability before (moderate = 65.20%, and low = 34.80%) and after (good = 56.52%, moderate = 39.13%, and low = 4.35%) the family promoting program for self-management of older persons with knee osteoarthritis on fall prevention increased. After participating in the program, participants showed a statistically significant higher level of balance and walking ability (z = -4.47, p<0.001). The results of this study reveal that the effect of the family promoting program for self-management of older persons with knee osteoarthritis on fall prevention can reduce the level of risk of falling and enhance a level of balance and walking ability. The results will be beneficial for community nurses and health care teams to use as a guideline to promote family intervention and support for older persons with knee osteoarthritis in the community in order to self-manage and prevent falls.